Philosophical Meaning in Sunda Banten Traditional Wedding Rituals - Moh. Annur Tri Putra; Finsa Adhi Pratam; Karim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The traditional wedding ritual of Sunda Banten, especially in Kalang Anyar Village, Serang City, Banten, is a hereditary tradition inherent in the community, they believe in the meaning contained in each series of traditional wedding rituals for their survival. The Sunda Banten traditional wedding ritual is part of a cultural symbol with philosophical values ??inherited by their predecessors and this ritual is believed to have a small impact on the life that is carried out. So it is considered necessary to examine the traditional Sunda Banten wedding rituals in the symbols and philosophical meanings they contain. This research is a qualitative field research by using phenomenology as an approach that allows researchers to better understand the behavior and perception of objects. The conclusion obtained from this research is that the overall philosophical meaning in the series of traditional Sunda Banten wedding ceremonies in Kalang Anyar that the various symbols used in the Sunda Banten traditional wedding rituals are as a form of gratitude to Allah Ta'ala for having met their soul mate as well as a vessel in strengthen social relations between fellow human beings and in the context of preserving culture that is valuable for the survival of the community.